2012
DOI: 10.1371/journal.pone.0049437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reef Proximity on the Structure of Fish Assemblages of Unconsolidated Substrata

Abstract: Fish assemblages of unconsolidated sedimentary habitats on continental shelves are poorly described when compared to those of hard substrata. This lack of data restricts the objective management of these extensive benthic habitats. In the context of protecting representative areas of all community types, one important question is the nature of the transition from reefal to sedimentary fish assemblages. We addressed this question using Baited Remote Underwater Videos (BRUVs) to assess fish assemblages of sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…The positive influence of surface rugosity on the abundance of piscivores and sediment infauna predators may relate to the influence on their prey. Piscivores may benefit from surface rugosity because it increases the availability of their prey; while sediment infauna predators may find a habitat with more patches of sand around reef edges has higher abundance of their prey, compared to sandy areas further away from reefs, and also provides quicker access to shelter (Schultz et al 2012). The negative influence of surface rugosity on herbivores likely relates to advantages Table 4.…”
Section: The Influence Of Habitat Structural Complexity On Fish Abundmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive influence of surface rugosity on the abundance of piscivores and sediment infauna predators may relate to the influence on their prey. Piscivores may benefit from surface rugosity because it increases the availability of their prey; while sediment infauna predators may find a habitat with more patches of sand around reef edges has higher abundance of their prey, compared to sandy areas further away from reefs, and also provides quicker access to shelter (Schultz et al 2012). The negative influence of surface rugosity on herbivores likely relates to advantages Table 4.…”
Section: The Influence Of Habitat Structural Complexity On Fish Abundmentioning
confidence: 99%
“…Understanding relationships between habitat complexity and fish assemblages, as surrogates for biodiversity patterns, will benefit management planning, especially as high-resolution seabed terrain data become available (Ierodiaconou et al 2007, Todd andKostylev, 2011). High-resolution data is capable of capturing heterogeneity across multiple spatial extents and therefore should be incorporated into spatial ecology and conservation planning, as suggested in other studies (Valentine et al 2007, Vanderklift et al 2007, Schultz et al 2012). This study demonstrated that high-resolution surface rugosity is a useful measure that explained on average 16% of the variance in fish abundance, whereas the mean amount of variance explained by the main predictor of interest in ecological studies is typically between 2.5-5.4% (Møller and Jennions 2002).…”
Section: Management Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, preliminary BRUVs data, both from an examination of the effects of proximity to reef on fish assemblages [30], and from haphazard deployment across the SIMP (Malcolm, unpublished data), suggest a substantially different suite of species to those found on rocky reefs.…”
Section: Introductionmentioning
confidence: 99%
“…A dummy variable with a species value of 1 was added to each sample, for all analyses, to account for undefined values as a result of the absence of fishes along some RVCs (Monk et al ., ). All univariate analyses outlined below were based on Euclidian distance (Schultz et al ., ) and all multivariate analyses on Bray‐Curtis distance measures. Monte‐Carlo P ‐values (Anderson, ) were used for all analyses both univariate and multivariate where there was an insufficient number of unique permutations for estimates of P ‐values.…”
Section: Methodsmentioning
confidence: 97%